A carbohydrate epitope expressed uniquely on the cell surface of Drosophila neurons is altered in the mutant nac (neurally altered carbohydrate). - Katz, F (1988)
Antibodies against horseradish peroxidase (anti-HRP) recognize neural specific cell surface antigens in Drosophila and other insects. The nature of these antigens was investigated in Drosophila and found to include a complex set of developmentally regulated proteins. Their common epitope appears to be a carbohydrate that shares features with the sugar moiety of pineapple stem bromelain, a plant glycoprotein whose carbohydrate structure has been determined. A mutation was identified that eliminates staining by the antibody in imaginal and adult neural tissue. Tissue specific glycoconjugates, although widespread in the animal kingdom, are little understood. This mutation provides a unique opportunity to address the consequences of altering a neural specific carbohydrate moiety in an otherwise intact and behaving animal. The mutation maps to 84F. A second mutation, contained on the third chromosome balancer, TM3, eliminates anti-HRP staining in embryos. These mutations appear to be separate genes.